Cranberry Proanthocyanidins Improve the Gut Mucous Layer Morphology and Function in Mice Receiving Elemental Enteral Nutrition. Issue 3 (11th October 2012) - Pierre, Joseph F.; Heneghan, Aaron F.; Feliciano, Rodrigo P.; Shanmuganayagam, Dhanansayan; Roenneburg, Drew A.; Krueger, Christian G.; Reed, Jess D.; Kudsk, Kenneth A.
Abstract : Background: Lamina propria Th2 cytokines, interleukin (IL)‐4 and IL‐13, stimulate goblet cell (GC) proliferation and MUC2 production, which protect the intestinal mucosa. Elemental enteral nutrition (EEN) reduces tissue IL‐4 and impairs barrier function. Proanthocyanidins (PACs) stimulate oral mucin levels. We hypothesized that adding PAC to EEN would maintain Th2–without stimulating Th1–cytokines and preserve luminal MUC2 vs EEN alone. Materials and Methods: Seventy mice were randomized to 5 diet groups–standard chow, intragastric EEN, or EEN with lowPAC, midPAC (50 mg), or highPAC (100 mg PAC/kg BW)–for 5 days, starting 2 days after gastric cannulation. Ileal tissue was analyzed for histomorphology and the cytokines IL‐4, IL‐13, IL‐1β, IL‐6, and TNF‐α by enzyme‐linked immunosorbent assay. MUC2 was measured in intestinal washes. Results: EEN lowered IL‐13 (P < .05) compared with standard chow, whereas IL‐4 was not significant (P < .07). LowPAC and midPAC increased IL‐13 (P < .05), whereas highPAC increased both IL‐4 and IL‐13 (P < .05) compared with EEN. All EEN diets reduced (P < .05) crypt depth compared with the chow group. Compared with standard chow, GC numbers and luminal MUC2 were reduced with EEN (P < .05). These effects were attenuated (P < .05) with midPAC and highPAC. No changes were observed in tissue Th1 cytokines. Conclusions: Adding PACs to EEN reverses impaired intestinal barrier function following EEN by improving the gut mucous layer and function through increased GC size and number as well as levels of MUC2 and ileal IL‐4 and IL‐13.